A comparative consecutive case series of 20 children with a diagnosis of ADHD receiving homeopathic treatment, compared with 10 children receiving usual care. Issue 2 (May 2016) - Fibert, Philippa; Relton, Clare; Heirs, Morag; Bowden, Deborah
Abstract : 20 consecutively enrolled children age 5–16 with Attention Deficit Hyperactivity Disorder (ADHD) received treatment by a homeopath (8 consultations and individualized remedies) for one year. Ten subsequently enrolled children received similar time and attention for 4 months. The study explored optimum treatment protocols; the effectiveness, deliverability and acceptability of treatment; and the feasibility of outcome measurement and recruitment. Parents completed Conners' Parent Rating Scale, Revised Long Version (CPRS-R:L) every 4 months, from which DSMIV total scores were extracted; and Measure Your Own Medical Outcome Profile (MYMOP) every consultation. An interaction between time (baseline/4 months) and group (treatment/non-treatment) was found .756 F (1, 28) = 9.06, p = 0.005. The intervention was associated with statistically significant improvements in treated children over the year: CPRS-R:L (t (18) = 4.529, p ≤ 0.000); MYMOP (t (18) = 6.938, p ≤ 0.000). Mean DSMIV total t scores decreased at each time point: baseline: 85 (SD 5.1); 4 months 76.2 (SD 10.9); and 12 months 71.5 (SD 12.77). Recruitment of control participants was problematic. Recruitment to treatment was feasible via ADHD support groups, charities, police support agencies and social services, not schools or NHS services. Attending appointments was problematic for some participants, but home visits did not improve uptake. The best venue was a familiar clinic. Some participants took medicines inappropriately, but generally taking homeopathic remedies was acceptable and well implemented. CPRS-R:L (80 items) was problematic for some parents. MYMOP was preferred by parents but not acceptable to stakeholders. In this small consecutive sample the intervention was associated with improvements in criminality, anger and children with a concomitant diagnosis of Autism Spectrum Disorder ASD. Treatment by a homeopath was associated with sustained, increasing improvements and the intervention was acceptable to participants. More methodically rigorous research is warranted. "We recommend that future research in this area uses comparative effectiveness randomised controlled trial designs. We also recommend that these trials measure outcomes of relevance to stakeholder needs – the people and services who care for those with ADHD – parents, teachers and social workers and the criminal justice system". Highlights: Treatment by a homeopath was associated with improvements in ADHD symptoms. No improvements were seen in children receiving similar time and attention. Treated children's symptoms continued to improve during one year. Recruitment, outcome measurement and the intervention were feasible. A novel homeopathic methodology was particularly effective where indicated.